Exchange rate stability and import penetration: The case of Malaysia and Singapore - Teo, Tyson Chih Soon (Universiti Malaysia Sarawak, (UNIMAS), 2013)
In this research, the relationship of nominal exchange rate stability and import penetration between Malaysia (developing economy) and Singapore (developed economy) are being examined. The time series data employed in this research consist of annual data ranging from year 1980 to 2010. The methodology applied in this research comprises of Augmented Dickey Fuller (ADF) unit root test, Johansen and Juselius cointegration test as well as Granger causality test based on Vector Error Correction Model (VECMY In the cases for both countries under review, the Co integration test shows that there is an existence of long run equilibrium linkage between both variables employed. Also, in short run, the Granger causality test shows a positive bi-directional relationship from the independent variable (nominal exchange rate stability) to dependent variable (import penetration ratio). Though the relationship of both variables is similar between both countries, the degree of its relationship varies.